DESIGN OF SCHOOL INFORMATION SYSTEMS USING THE TOGAF ADM METHOD AT SMKN 1 KEMLAG - Muhamad Irfan Fanani; Eman Setiawan (Universitas Trunojoyo Madura, 2022)
In the process of developing the right information system, of course, there are several aspects that need to be considered. For example, the development of the system has an enterprise architecture basis, which has a pattern in terms of planning, designing, and managing the information system itself. For now, SMK NEGERI 1 KEMLAGI has not integrated information systems in both academic and non-academic fields such as administrative management, library management and school facilities and infrastructure. All activities carried out have been assisted by the existence of IT infrastructure such as computers and networks, but this is not enough to adapt to the dynamic development of application technology. Based on these problems, an architectural design is needed that can be a solution for academic and non-academic information system management. The design uses the TOGAF ADM method, this method is known to be complete and easy to use. In the application of TOGAF ADM, a good understanding of the business processes of the relevant organizations must be mastered. So that it can provide a good guide for creating a blueprint for the required information system components